Peranan Need to Belong terhadap Hubungan Interpersonal pada Remaja - Hafizoh, Hafizoh; Febriani, Risna; Rifandi, Akhmad (Jurnal Ilmiah Psikomuda (JIPM) Connectedness, 2023)
Abstract. This study aims to examine the role of need to belong to interpersonal relationship in adolescents. The reseach method used is a quantitative method with correlational design. The data collection tool used is the need to belong scale and interpersonal relationship. The subject taking technique used purposive sampling with the criteria of adolescents aged 16–20 years who have friends in the city of Banjarmasin. The total subjects is 234. The data analysis used is simple linear regression analysis. The results showed that need to belong significantly predict interpersonal relationship in adolescents. Need to belong can play a role in predicting interpersonal relationship by 41% (R2=0,410; sig < 0,000). Based on these results, the research hypothesis is accepted, namely that there is a role of need to belong to interpersonal relationship ini adolescents.